2017
DOI: 10.1111/1365-2656.12640
|View full text |Cite
|
Sign up to set email alerts
|

Competitor phenology as a social cue in breeding site selection

Abstract: Summary 1.Predicting habitat quality is a major challenge for animals selecting a breeding patch, because it affects reproductive success. Breeding site selection may be based on previous experience, or on social information from the density and success of competitors with an earlier phenology. 2. Variation in animal breeding phenology is often correlated with variation in habitat quality. Generally, animals breed earlier in high-quality habitats that allow them to reach a nutritional threshold required for br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 55 publications
7
42
1
Order By: Relevance
“…The low female contribution to the joint phenotype observed here contrasts with another recent experimental study in the pied flycatcher, where only females used tit phenology as a source of social information for breeding site selection (Samplonius and Both, 2017). Even though our study is not directly comparable with that of Samplonius and Both (2017), both report differences between sexes in social information use for breeding site selection, and our results also suggest a differential effect of individual experience as reflected by age and dispersal status between sexes. Such between-sex differences may result from sex-specific information gathering processes (Reed et al, 1999;Doligez et al, 2004b), in relation to sex-specific fitness benefits associated with breeding system and dispersal processes (Greenwood, 1980).…”
Section: The Role Of Experience In Social Information Usecontrasting
confidence: 99%
See 2 more Smart Citations
“…The low female contribution to the joint phenotype observed here contrasts with another recent experimental study in the pied flycatcher, where only females used tit phenology as a source of social information for breeding site selection (Samplonius and Both, 2017). Even though our study is not directly comparable with that of Samplonius and Both (2017), both report differences between sexes in social information use for breeding site selection, and our results also suggest a differential effect of individual experience as reflected by age and dispersal status between sexes. Such between-sex differences may result from sex-specific information gathering processes (Reed et al, 1999;Doligez et al, 2004b), in relation to sex-specific fitness benefits associated with breeding system and dispersal processes (Greenwood, 1980).…”
Section: The Role Of Experience In Social Information Usecontrasting
confidence: 99%
“…These sex-specific selective pressures acting on the knowledge of the environment and information gathering may translate into the use of different information sources (including social information) between sexes and/or differential use of the same information depending on individual experience, as suggested here. Both our results and previous results (Samplonius and Both, 2017) are coherent with a preponderant use of fine-scale social information by males and large-scale social information by females. Estimates for the selected fixed and random effects are presented for the male and female full models, and for the selected model for females.…”
Section: The Role Of Experience In Social Information Usesupporting
confidence: 91%
See 1 more Smart Citation
“…It is generally shown that resident species are more plastic in their response to temperature than migrants (Phillimore et al, ; Samplonius et al, ), causing their breeding phenologies to diverge. Such differential divergence has been shown to affect information use (Samplonius & Both, ), and here I show it could affect competitive interactions. This could mean that arriving competitors will encounter fewer aggressive great tits as climate change continues, because great tits advance their breeding phenology more than later breeding migrants in response to temperature (Samplonius et al, ).…”
Section: Discussionsupporting
confidence: 61%
“…Responses in laying or hatching date are often interpreted in relation to the phenology of underlying trophic levels, but it is important to consider that also changes in interspecific competitor timing (Samplonius & Both, ) could act as selection pressures that determine the optimal timing response. European tits and flycatchers are ideal model species to study differential adjustment to climate change.…”
Section: Introductionmentioning
confidence: 99%